Emerging trends in taxonomy research and evolutionary systematics of fish fauna of North-East India - VISHWANATH, W; LINTHOINGAMBI, I (The Indian Journal of Animal Sciences, 2010)
The importance of taxonomy and systematics lies not only in making the information on diversity of organisms accessible, but also in planning for their conservation and sustainable use. Present taxonomy study involves understanding of inter-basin connections in the past, and drainage basin concept in case of freshwater fishes, tectonic setup of a particular region. Naming and availability of species should strictly conform to the Code. Molecular approaches have become useful in phylogenetic analyses, but the real taxonomy should not be decimated. North-East India is rich in fish diversity due to various factors. However, the diversity is still in the discovery survey state. Phylogenetic studies of the fishes with the prevailing concepts would come out with interesting results.